Ethical dilemmas in international criminological research - Adorjan, Michael; Ricciardelli, Rose, 1979- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2023)
Building on the editors' previous publication, Engaging with Ethics in International Criminological Research, this new book brings together a fresh collection of leading international scholars tackling ethical dilemmas in criminological research. Contributors address how they have experienced and addressed ethical issues in their research, and how they have balanced the benefits and harms of doing such research for both the researcher and the researched. Ethical Dilemmas in International Criminological Research draws on various issues across a range of jurisdictions and political and social contexts, including cybercrime and transgressive online actions; state and police responses to crime; the war on drugs; working with traumatised participants in criminological research; punishment and prison; and sex, sexualities, and gender. Moreover, this collection aims to offer a truly international perspective, including insights from research projects in the Global South. This book is essential reading for junior scholars just starting out with original research, as well as more seasoned researchers looking to gain insights into the challenges of criminological research in other cultural contexts. It is also instructive reading for students taking courses in criminological and social research methods.
OCLC-licensed vendor bibliographic record.
Keywords: Criminology -- Research -- Moral and ethical aspects; PHILOSOPHY / Ethics & Moral Philosophy; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Methodology